FAKTOR YANG MEMPENGARUHI PENGUNJUNG MILENIAL KE PANTAI CINTA KEDUNGU, KABUPATEN TABANAN - Suci Septia, Hesy; Sofia Wijaya, Ni Made; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022)DO - 10.24843/IPTA.2022.v10.i02.p16, 2023)
The number of visitors that visited Cinta Beach Kedungu has increased since it was opened on September 2020. This study aims to determine the factors that affecting millennial visitors decision to visit Cinta Beach Kedungu. The sample of this research was 130 millennial visitors who have visited Cinta Beach Kedungu. Data collection techniques was conducted in several ways, such as: observation, questionnaire, interview, literature study, and documentation. The data were analysed by factor analysis. The results showed that the characteristics of the respondents were dominated by visitors from Denpasar, women, aged 21-25 years, unmarried, level of education was bachelor degree, status as student, visited Cinta Beach Kedungu with friends on weekends, and spend Rp. 101-200 thousands. Based on the results of factor analysis, there are six push factors that affecting visitors, such as: (1) looking for a partner, (2) looking for novelty, (3) spending time with family, (4) breaking away from routine, (5) visiting famous places on social media and (6) romanticism. Meanwhile, three pull factors that affecting visitors such as: (1) facilities and products, (2) information about tourist attractions, and (3) natural beauty.